Natural Compounds against Cancer, Inflammation, and Oxidative Stress - Tabolacci, Claudio; Forni, Cinzia; Jadeja, Ravirajsinh N.; Facchiano, Francesco (BioMed research international, 2019)
[...]several active herbal compounds are tested in human clinical trials, used as adjuvants with conventional anticancer therapies in order to reduce side effects like nausea and fatigue [4]. [...]a considerable number of studies reported the use of natural compounds for their anti-inflammatory activity, since inflammation is considered the basis of various disease conditions, including cancer. The use of herbal preparation in combination with suitable diet represents also one of the most promising strategies to treat metabolic disorders like diabetes, obesity, and metabolic syndrome [5]. [...]due to their several biological activities, natural compounds represent good candidates for preventing and even curing the effects of neurodegenerative diseases.